RNA and DNA Editing Methods and Protocols - Aphasizhev, Ruslan.; Aphasizhev, Ruslan. (Methods in Molecular Biology,, 2011)
The recent expansion in diversity of RNA and DNA editing types has stimulated the development of many unique genetic, molecular, biochemical, and computational approaches to biological issues.  In RNA and DNA Editing: Methods and Protocols, leading experts in the field introduce methods developed over the last few years to study editing substrates, mechanisms of specificity, and functions of RNA and DNA editing enzymes and complexes. Sections of the book are dedicated to state-of-the art techniques which enable investigation of uracil insertion/deletion RNA editing in mitochondrion of Trypanosoma brucei, adenosine to inosine RNA editing, cytidine to uracil RNA and DNA editing, as well as tRNA editing and RNA modifications.  Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and cutting-edge, RNA and DNA Editing: Methods and Protocols seeks to inspire the further development of these vital and powerful techniques.